PEMBERDAYAAN MASYARAKAT BERBASIS KOMUNITAS UNTUK PENGELOLAAN SAMPAH PLASTIK DI PULAU PRAMUKA - Nike Vonika; Versanudin Hekmatyar (Pekerjaan Sosial, 2022)
As the population increases from year to year and is accompanied by a high intensity of human activities, resulting in an increase in the amount of waste piles. Good waste management and processing is currently still very minimal so that it has an impact on environmental pollution which in turn affects the sustainability of human life. Meanwhile, environmental factors are one of the determining factors in determining the quality of people’s lives. This study describes qualitatively the process of community empowerment related to handling environmental problems, namely waste management, especially plastic waste on Pramuka Island. This empowerment is a collaboration between the Get Plastic Foundation and the Green Literacy House in building a waste management system and involving the community as a whole. First, waste handling is carried out by processing plastic waste into fuel (diesel) using a pyrolysis machine developed by Get Plastic. Second, by socializing and educating the public so that they have awareness in protecting the environment. The result of the empowerment carried out is that Pramuka Island can significantly reduce its plastic waste because it can be processed into energy that can be used directly.